Four new species of Cichlidogyrus (Monogenea, Ancyrocephalidae) from Sarotherodon mvogoi and Tylochromis sudanensis (Teleostei, Cichlidae) in Cameroon - Pariselle, Antoine; Nyom, Arnold R. Bitja; Bilong, Charles F. Bilong (Zootaxa, 2014)
The four Cichlidogyrus species (Monogenea, Ancyrocephalidae) found on the gills of Sarotherodon mvogoi and Tylochromis sudanensis (Teleostei, Cichlidae) in Cameroon are considered new and are described herein. Cichlidogyrus mvogoi n. sp. from Sarotherodon mvogoi, characterised by a long (> 100 µm), thin and spirally coiled penis and a short marginal hook pair I. Cichlidogyrus sigmocirrus n. sp. from Tylochromis sudanensis, characterised by a short marginal hook pair I, a slightly spirally coiled penis with reduced heel, an accessory piece being a spirally coiled band wrapped round the penis and attached to the penis basal bulb by a very thin filament. Cichlidogyrus chrysopiformis n. sp. from Tylochromis sudanensis, characterised by an marginal hook pair I of medium size, a thin spirally coiled penis (1.5 turn) with a developed flared heel, an accessory piece being a large gutter shaped band, ending in a narrow complex extremity, and linked to the basal bulb of the penis by a very thin filament, a short, straight and slightly ringed vagina. Cichlidogyrus djietoi n. sp. from Tylochromis sudanensis, characterised by a slightly spirally coiled penis (2 turns) with developed heel, an accessory piece being a large gutter shaped band, ending in a narrow folded back extremity, a short funnel shaped vagina. The three latter species are also remarkable by the morphology of their auricles implanted on the anterior side of the dorsal transverse bar which make them (together with the other species described from Tylochromis hosts) a homogeneous and original group within Cichlidogyrus, this distinctive feature seems to be ancestral compared to other Cichlidogyrus species.